KELIMPAHAN DAN KEANEKARAGAMAN KUPU-KUPU DI KECAMATAN TUGUMULYO KABUPATEN MUSI RAWAS - Septiana Septiana; Tiara Yulisah; Dian Samitra (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2019)
This study aims to determine the abundance and diversity of butterflies in Tugumulyo District, Musi Rawas Regency. The study uses exploratory survey methods. Sampling is carried out from 8:00 to 10:00 and 14:00 to 17:00. Butterflies are captured using insect nets. Butterflies obtained are preserved dry to be identified and made into an insectarium. Identification of insects based on the key to determination. Research data includes butterfly species, the number of each species. Data is processed to determine the value of relative abundance, diversity index, dominance and evenness. The results showed that in Tugumulyo Subdistrict there were 49 species, belonging to 5 families: Papilionidae, Nymphalidae, Lycaenidae, Hesperidae and Pieridae. The butterfly species which has the highest abundance is Hympolimnas bolina Linnaeus (Nymphalidae), with a relative abundance of 9.79%. Butterfly ecology index in Tugumulyo District: diversity index 3.19, dominance 0.82 and evenness 1.0. Keywords: Abundance, Diversity, Butterflies